TANK Promotes Pressure Overload Induced Cardiac Hypertrophy via Activating AKT Signaling Pathway - Pang, Yanan; Ma, Minglu; Wang, Dong; Li, Xun; Jiang, Li (Frontiers in Cardiovascular Medicine, 2021)
Background— TANK (TRAF family member associated NF-κB activator) acts as a member of scaffold proteins participate in the development of multiple diseases. However, its function in cardiac hypertrophy is still unknown. Methods and Results— In this study, we observed an increased expression of TANK in murine hypertrophic hearts after aortic banding, suggesting that TANK may be involved in the pathogenesis of cardiac hypertrophy. We generated cardiac-specific TANK knockout mice, and subsequently subjected to aortic banding for four to eight weeks. TANK knockout mice showed attenuated cardiac hypertrophy and dysfunction compared to the control group. In contrast, cardiac-specific TANK transgenic mice showed opposite signs. Consistently, in vitro experiments revealed that TANK knockdown dramatically decreased the cell size and expression of hypertrophic markers. Mechanistically, AKT signaling was inhibited in TANK knockout mice, but activated in TANK transgenic mice after aortic banding. Blocking AKT signaling with a pharmacological AKT inhibitor alleviated the cardiac hypertrophy and dysfunction in TANK transgenic mice. Conclusions— Collectively, we identified TANK accelerate the progression of pathological cardiac hypertrophy and a potential therapeutic target. Key words: TANK; Cardiac hypertrophy; Transgenic mice; AKT signaling